French in language has a lot meaningful of words and semantic features (Eurasian Journal of Learning and Academic Teaching, 2023)
French language polysemantic words are complicated and interesting aspects and not only French linguists, but perhaps in general language diversity, the attention of researchers pulls. In the article we are French in the language polysemantic of words semantic their characteristics meanings and contextualization in detail seeing we go out We are polysemantic of words one how many examples analysis we do, their meaning, different context and situations application forms as well them in the understanding of context role learned, as well as polysemantic the words in understanding contextualization and of context place and they are to the context looking of the word the meaning how to change about let's talk This in the article I am polysemantic the words learning for different of methods I used, for example, linguistic texts analysis to do and contextual analysis to make as well as different the authors and of researchers comparative from the analysis. Polysemantic the words literature and language in their games apply to pay attention to the methods I looked at it they’re a lot of edged and variability open gives. My research not only French language learners for maybe in general language diversity semantics and lexicology with interested linguists and researchers also useful for will be I semantics in research and lexicology in the field famous of authors from his works I used this to me, French, language polysemantic words deeper to understand enable gave